Control of speed-strength load in training of skiers-racers based on the application of tools - Vasilyeva, V. S.; Dorozhko, A. S.; Karaseva, T. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to experimentally substantiate the use of feedback tools in the operational control of speed-strength loads in the training of highly qualified ski racers.